Characterisation of the serum cytokine profile in feline atopic skin syndrome. Issue 5 (27th June 2021) - Vargo, Cheryl; Gogal, Robert; Barber, James; Austel, Michaela; Banovic, Frane
Abstract : Background: Feline atopic skin syndrome (FASS) is a pruritic and inflammatory skin disease commonly encountered in cats. Three previous reports evaluated cytokine immune activation in cats diagnosed with feline allergic dermatitis. However, no significant upregulations were observed in allergic cats compared to healthy controls. Hypothesis/Objective: To evaluate differences in the serum cytokine profile of cats diagnosed with FASS compared to healthy cats, and correlate serum markers with the extent of FASS skin disease using clinical scoring systems. Animals: Thirteen client‐owned FASS cats and 12 healthy control cats. Methods and materials: Thirteen cytokine and chemokines from the serum of FASS cats and healthy controls were analysed using a commercially available feline‐specific multiplex assay. Results: Patients with FASS had a significant increase in serum concentrations of interferon‐gamma (IFN‐γ), interleukin (IL)‐2, IL‐13 and IL‐18. In addition, cytokine/chemokines involved in inflammation and chemotaxis [IL‐8, C‐C Motif Chemokine Ligand (CCL)5, CCL2 and CXCL12], as well as growth factors, stem cell factor and Fms‐related tyrosine kinase 3 ligand (Flt3L), also were significantly elevated. A significant positive correlation ( r  = 0.64) between the serum levels of Flt3L and Scoring Feline Allergic Dermatitis (SCORFAD) score was observed. Conclusions: These results demonstrate the activation of a broad array of immune secretory cytokines in the serum of cats with FASS, which are largely associated with a mixed Th1 and Th2 inflammatory response along with specific growth factors. Further larger‐sample studies are needed to assess the modulation of serum biomarkers in FASS by pharmacological/therapeutic interventions. Abstract : Background – Feline atopic skin syndrome (FASS) is a pruritic and inflammatory skin disease commonly encountered in cats. Three previous reports evaluated cytokine immune activation in cats diagnosed with feline allergic dermatitis. However, no significant upregulations were observed in allergic cats compared to healthy controls. Hypothesis/Objective – To evaluate differences in the serum cytokine profile of cats diagnosed with FASS compared to healthy cats, and correlate serum markers with the extent of FASS skin disease using clinical scoring systems. Conclusions – These results demonstrate the activation of a broad array of immune secretory cytokines in the serum of cats with FASS, which are largely associated with a mixed Th1 and Th2 inflammatory response along with specific growth factors. Further larger‐sample studies are needed to assess the modulation of serum biomarkers in FASS by pharmacological/therapeutic interventions. Résumé: Contexte: Le syndrome atopique cutané félin (FASS) est une dermatose inflammatoire et prurigineuse fréquente du chat. Trois articles précédents ont évalué l'activation des cytokines immunitaires chez les chats avec dermatite allergique féline. Cependant, aucune augmentation significative n'a été observée chez les chats allergiques comparés aux contrôles sains. Hypothèses/Objectifs: Evaluer les différences de profils cytokiniques des chats diagnostiqués avec FASS comparé aux chats sains et corréler les marqueurs sériques selon la gravité de FASS à l'aide de système de notation clinique. Sujets: Treize chats FASS de propriétaires et 12 chats sains contrôles. Matériels et méthodes: Treize cytokines et chimiokines du serum de chats FASS et de chats contrôles sains ont été analysées à l'aide de test multiplexe spécifique du chat disponible dans le commerce. Résultats: Les patients avec FASS avaient une augmentation significative des concentrations sériques d'interféron gamma (IFN‐γ), d'interleukine (IL)‐2, IL‐13 et IL‐18. En outre, les cytokines/chimiokines impliquées dans l'inflammation et le chimiotaxis [IL‐8, C‐C Motif Chemokine Ligand (CCL)5, CCL2 et CXCL12], ainsi que les facteurs de croissance, stem cell factor et Flt3L (Fms‐related tyrosine kinase 3 ligand), aussi étaient significativement élevé. Une corrélation significative positive (r = 0.64) entre les niveaux sériques de Flt3L et le SCORFAD (Scoring Feline Allergic Dermatitis) a été observée. Conclusions: Ces résultats démontrent que l'activation d'un large spectre de cytokines sécrétantes immunitaires dans le serum de chats avec FASS, qui sont largement associées avec une réponse inflammatoire, mélange de Th1 et Th2, correspond à des facteurs de croissance spécifiques. Davantage d'études larges sont nécessaires pour la modulation de biomarqueurs sériques chez FASS par interventions thérapeutique/pharmacologique. Resumen: Introducción: el síndrome de la piel atópica felina (FASS) es una enfermedad cutánea pruriginosa e inflamatoria que se describe comúnmente en gatos. Tres publicaciones anteriores evaluaron la activación inmune de citoquinas en gatos diagnosticados con dermatitis alérgica felina. Sin embargo, no se observaron elevaciones significativas en gatos alérgicos en comparación con controles sanos. Hipótesis/objetivo: evaluar las diferencias en el perfil de citoquinas séricas de gatos diagnosticados con FASS en comparación con gatos sanos, y correlacionar los marcadores séricos con la extensión de la enfermedad cutánea FASS mediante sistemas de valoración clínica. Animales: trece gatos con FASS de propietarios particulares y 12 gatos control sanos. Métodos y materiales: Se analizaron trece citoquinas y quimioquinas del suero de gatos con FASS y controles sanos utilizando un ensayo multiplex específico para felinos disponible comercialmente. Resultados: los pacientes con FASS tuvieron un aumento significativo en las concentraciones séricas de interferón‐gamma (IFN‐γ), interleuquina (IL)‐2, IL‐13 e IL‐18. Además, citoquinas /quimioquinas involucradas en la inflamación y la quimiotaxis [IL‐8, CC Motif Chemokine Ligand (CCL) 5, CCL2 y CXCL12], así como factores de crecimiento, factor de células madre y ligando de tirosina quinasa 3 relacionado con Fms (Flt3L), también estuvieron significativamente elevados. Se observó una correlación positiva significativa (r = 0, 64) entre los niveles séricos de Flt3L y la valoración de dermatitis alérgica felina (SCORFAD). Conclusiones: estos resultados demuestran la activación de una amplia gama de citoquinas secretoras inmunes en el suero de gatos con FASS, que se asocian en gran medida con una respuesta inflamatoria mixta Th1 y Th2 junto con factores de crecimiento específicos. Se necesitan más estudios con muestras más grandes para evaluar la modulación de los biomarcadores séricos en gatos con FASS mediante intervenciones farmacológicas/terapéuticas. Zusammenfassung: Hintergrund: Das Feline Atopische Hautsyndrom (FASS) ist eine juckende und entzündliche Hauterkrankung, die bei Katzen häufig auftritt. Drei frühere Berichte untersuchten die Zytokin Immunaktivierung bei Katzen, die mit allergischer Dermatitis diagnostiziert worden waren. Es wurde jedoch keine signifikante Erhöhung bei allergischen Katzen im Vergleich zu gesunden Kontrollen festgestellt. Hypothese/Ziel: Eine Evaluierung der Unterschiede beim Serum Zytokinprofil von Katzen, die mit FASS diagnostiziert worden waren, im Vergleich zu gesunden Katzen sowie ein Vergleich der Serummarker mit dem Schweregrad der FASS Hauterkrankung mittels klinischem Scoring System. Tiere: Dreizehn FASS Katzen in Privatbesitz und 12 gesunde Kontrollkatzen. Methoden und Materialien: Dreizehn Zytokine und Chemokine aus dem Serum von FASS Katzen und gesunden Kontrolltieren wurden mittels kommerziell erhältlichem Katzen‐spezifischem Multiplex Assay analysiert. Ergebnisse: Patienten mit FASS zeigten signifikant höhere Serumkonzentrationen an Interferon‐gamma (IFN‐γ), Interleukin (IL)‐2, IL‐3 und IL‐18. Zusätzlich waren Zytokine/Chemokine, die bei Entzündung und Chemotaxis eine Rolle spielen [IL‐8, C‐C Motif Chemokin Ligand (CCL)5, CCL2 und CXCL12] sowie Wachstumsfaktoren, Stammzellenfaktor und Fms‐related Tyrosin Kinase 3 Ligand (Flt3L) signifikant erhöht. Es wurde eine signifikante positive Korrelation ( r = 0, 64) zwischen den Serumwerten von Flt3L und dem Scoring Feline Allergic Dermatitis (SCORFAD) Score beobachtet. Schlussfolgerungen: Diese Ergebnisse zeigen die Aktivierung einer breiten Palette an Immun‐sekretorischen Zytokinen im Serum von Katzen mit FASS, die weitgehend mit einer gemischten Th1 und Th2 Entzündungsantwort zusammen mit speziellen Wachstumsfaktoren einhergehen. Es sind weitere Studien mit größeren Fallzahlen nötig, um die Modulierung der Serumbiomarker bei FASS durch pharmakologische/therapeutische Interventionen zu erfassen. 要約: 背景: 猫アトピー性皮膚症候群 (FASS) は、猫によく見られる痒みおよび炎症を伴う皮膚疾患である。過去に3つの報告があり、猫アレルギー性皮膚炎と診断された猫のサイトカイン免疫活性化を評価した。しかし、アレルギー体質の猫では、健常対照と比較して有意な上昇は認められなかった。 仮説/目的: 本研究の目的は、FASSと診断された猫の血清サイトカインプロファイルの違いを健常猫と比較評価し、臨床的なスコアリングシステムを用いて血清マーカーとFASS皮膚疾患の程度を相関させることであった。 供試動物: 顧客所有猫13頭のFASS猫および12頭の対照健常猫。 材料と方法: FASS猫および対照健常猫の血清中の13種類のサイトカインおよびケモカインを、市販の猫特異的マルチプレックスアッセイ法を用いて解析した。 結果: FASS患者では、インターフェロン‐ガンマ (IFNγ) 、インターロイキン (IL)‐2、IL‐13、IL‐18の血清濃度が有意に上昇していた。また、炎症や走化性に関与するサイトカイン/ケモカイン[IL‐8、C‐C Motif Chemokine Ligand (CCL)5、CCL2、CXCL12]や、成長因子である幹細胞因子、Fms関連チロシンキナーゼ3リガンド(Flt3L)も有意に上昇していた。Flt3Lの血清レベルとScoring Feline Allergic Dermatitis(SCORFAD) スコアの間には有意な正の相関関係 (r = 0.64) が認められた。 結論: これらの結果は、FASSを発症した猫の血清中で、幅広い免疫分泌サイトカインが活性化されていることを示しており、これらのサイトカインは、特定の成長因子とともに、主にTh1およびTh2の混合炎症反応と関連している。薬理学的・治療的介入によるFASSの血清バイオマーカーの変化を評価するには、さらに大規模なサンプルを用いた研究が必要である。 摘要: 背景: 猫特应性皮肤综合征(FASS)是猫常见的瘙痒性和炎性皮肤病。之前的三份报告评价了诊断为猫过敏性皮炎的猫, 其体内细胞因子免疫激活情况。然而, 与健康对照组相比, 在过敏猫中未观察到显著上调。 假设/目的: 评价诊断为FASS的猫与健康猫的血清细胞因子谱差异, 并使用临床评分系统将血清标志物与FASS皮肤病的程度相关联。 动物: 13只私家FASS猫和12只健康对照猫。 方法和材料: 使用市售猫特异性多重测定法分析FASS猫和健康对照血清中的13种细胞因子和趋化因子。 结果: FASS患猫血清γ‐干扰素(IFN‐)、白细胞介素(IL)‐2、IL‐13和IL‐18浓度显著升高。此外, 参与炎症和趋化的细胞因子/趋化因子[IL‐8、C‐C Motif趋化因子配体(CCL)5、CCL2和CXCL12], 以及生长因子、干细胞因子和Fms相关酪氨酸激酶3配体(Flt3L)也显著升高。观察到血清Flt3L水平与猫过敏性皮炎(SCORFAD)评分呈显著正相关(r = 0.64)。 结论: 这些结果表明FASS猫血清中免疫分泌细胞因子被广泛激活, 这在很大程度上与Th1和Th2混合炎性反应以及特异性生长因子相关。需要进一步的更大样本研究, 来评估药物/治疗干预对FASS中血清生物标志物的调节。 Resumo: Contexto: A síndrome atópica cutânea felina (SACF) é uma dermatopatia inflamatória e pruriginosa comumente encontrada em gatos. Três relatos anteriores avaliaram a ativação imune de citocinas em gatos diagnosticados com dermatite alérgica felina. Entretanto, não foram observadas ativações significativas em gatos alérgicos quando comparados com controles saudáveis. Hipótese/Objetivo: Avaliar as diferenças no perfil de citocinas sérico de gatos diagnosticados com SACF comparado com gatos saudáveis, e correlacionar os marcadores séricos com a extensão das lesões cutâneas da SACF utilizando sistemas de escores clínicos. Animais: Treze gatos de propriedade privada diagnosticados com SACF e 12 gatos controle saudáveis. Métodos e materiais: Treze citocinas e quimiocinas do soro dos gatos com SACF e dos controles saudáveis foram analisados utilizando um ensaio multiplex específico para felinos. Resultados: Pacientes com SACF apresentaram um aumento significativo nas concentrações séricas de interferon‐gama (IFN‐γ), interleucina (IL)‐2, IL‐13 e IL‐18. Além disso, as citocinas/quimiocinas envolvidas na inflamação e quimiotaxia [IL‐8, C‐C Motif Chemokine Ligand (CCL)5, CCL2 e CXCL12], bem como os fatores de crescimento, fator de célula tronco e Fms‐related tyrosine kinase 3 ligand (Flt3L), estavam também significativamente elevados. Observou‐se uma correlação positiva significativa ( r  = 0.64) entre os níveis séricos de Flt3L e o sistema de escore Scoring Feline Allergic Dermatitis (SCORFAD). Conclusões: Estes resultados demonstram a ativação de uma ampla variedade de citocinas secretórias no soro de gatos com SACF, que estão fortemente associadas com a resposta inflamatória Th1 e Th2 mista juntamente com fatores de crescimento específicos. São necessários mais estudos com uma quantidade maior de amostras para avaliar na SACF a modulação de biomarcadores séricos por intervenções farmacológicas/terapêuticas.